(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The hardness, impact strength and microstructure of 0.60%C plain carbon steel quenched-hardened in transesterified neem oil (TN) are reported in the study. Fresh neem oil (FN) was transesterified using methanol. Afterwards, steel samples normalized and then austenitized at 850oC for 40 minutes and then quenched in TN, FN and SAE40. The quenchant used as bench mark was SAE40. The as-quenched samples’ hardness and impact strength tested. Additionally, microstructural analysis on the as-quenched samples was carried out. TN-quenched sample exhibits higher hardness and impact strength as compared to FN-quenched parts. In all the quenched samples, martensite and retained austenite were observed. The investigation shows that TN gives good combination of hardness and impact strength. Therefore, TN is recommended to be used as quench medium for 0.60%C (AISI 1060) steel